An introduction to systematic reviews - Gough, David (David A.); Oliver, Sandy 1955-; Thomas, James 1983- (Los Angeles SAGE, 2017)
"Focused on actively using systematic review as method, An introduction to systematic reviews provides clear, step-by-step advice on the logic and processes of systematic reviewing. Stressing the importance of precision and accuracy, this practical text carefully balances a need for insightful theory with real-world pragmatism. The second edition features a new chapter on statistical synthesis and introduces a wide range of cutting-edge approaches to research synthesis, including text mining, living reviews, and new ideas in mixed methods reviews, such as qualitative comparative analysis"--Back cover.
Introducing systematic reviews / David Gough, Sandy Oliver and James Thomas -- Stakeholder perspectives and participation in reviews / Rebecca Rees and Sandy Oliver -- Commonality and diversity in reviews / David Gough and James Thomas -- Getting started with a review /Sandy Oliver, Kelly Dickson, Mukdarut Bangpan, and Mark Newman -- Finding relevant studies / Ginny Brunton, Claire Stansfield, Jenny Caird, and James Thomas -- Describing and analysing studies / Katy Sutcliffe, Sandy Oliver and Michelle Richardson -- Tools and technologies for information management / Jeff Brunton, James Thomas, and Sergio Graziosi -- Synthesis methods for combining and configuring textual or mixed methods data / James Thomas, Alison O'Mara-Eves, Angela Harden, and Mark Newman -- Synthesis methods for combining and configuring quantitative data / James Thomas, Alison O'Mara-Eves, Dylan Kneale and Ian Shemilt -- Developing justifiable evidence claims / Kristin Liabo, David Gough and Angela Harden -- Using research findings / David Gough, Ruth Stewart and Janice Tripney.
Includes bibliographical references (pages 297-322) and index.
Keywords: Research -- Methodology; Social sciences -- Research -- Methodology; Social sciences -- Research -- Evaluation